Plastid phylogenomics sheds light on divergence time and ecological adaptations of the tribe Persicarieae (Polygonaceae) - Cao, Dong-Ling; Zhang, Xue-Jie; Qu, Xiao-Jian; Fan, Shou-Jin (Frontiers in Plant Science, 2022)
Southwestern China, adjacent to the Qinghai-Tibetan Plateau (QTP), is known as a hotspot for plant diversity and endemism, and it is the origin and diversification center of Persicarieae. As one of the major lineages in Polygonaceae, Persicarieae represents a diverse adaptation to various habitats. As a result of morphological plasticity and poorly resolving molecular markers, phylogenetic relationships and infrageneric classification within Persicarieae have long been controversial. In addition, neither plastome phylogenomic studies nor divergence time estimates on a larger sample of Persicarieae species have been made thus far. We sequenced and assembled 74 complete plastomes, including all of the recognized genera within Persicarieae and their relatives. We conducted a comprehensive phylogenetic study of the major clades within Persicarieae and, based on the thus obtained robust phylogeny, also estimated divergence time and the evolution of diagnostic morphological traits. Major relationships found in previous phylogenetic studies were confirmed, including those of the backbone of the tree, which had been a major problem in previous phylogenies of the tribe. Phylogenetic analysis revealed strong support for Koenigia as sister to Bistorta, and together they were sister to the robustly supported Persicaria. Based on the phylogenetic and morphological evidence, we recognize five sections in Persicaria: Persicaria, Amphibia, Tovara, Echinocaulon, and Cephalophilon. It is estimated that the divergence of the Persicarieae began around the late Paleocene, with diversification concentrated in the Eocene and Miocene. In addition, it is suggested that the increasing westerly and monsoon winds in conjunction with the uplift of the QTP may be the driving force for origin and diversification of Persicarieae species. These results provide a valuable evolutionary framework for the study of adaptation in Polygonaceae and insights into plant diversification on the QTP and adjacent areas.